A bidirectional association between the gut microbiota and CNS disease in a biphasic murine model of multiple sclerosis. (2nd November 2017) - Colpitts, Sara L.; Kasper, Eli J.; Keever, Abigail; Liljenberg, Caleb; Kirby, Trevor; Magori, Krisztian; Kasper, Lloyd H.; Ochoa-Repáraz, Javier
ABSTRACT: The gut microbiome plays an important role in the development of inflammatory disease as shown using experimental models of central nervous system (CNS) demyelination. Gut microbes influence the response of regulatory immune cell populations in the gut-associated lymphoid tissue (GALT), which drive protection in acute and chronic experimental autoimmune encephalomyelitis (EAE). Recent observations suggest that communication between the host and the gut microbiome is bidirectional. We hypothesized that the gut microbiota differs between the acute inflammatory and chronic progressive stages of a murine model of secondary-progressive multiple sclerosis (SP-MS). This non-obese diabetic (NOD) model of EAE develops a biphasic pattern of disease that more closely resembles the human condition when transitioning from relapsing-remitting (RR)-MS to SP-MS. We compared the gut microbiome of NOD mice with either mild or severe disease to that of non-immunized control mice. We found that the mice which developed a severe secondary form of EAE harbored a dysbiotic gut microbiome when compared with the healthy control mice. Furthermore, we evaluated whether treatment with a cocktail of broad-spectrum antibiotics would modify the outcome of the progressive stage of EAE in the NOD model. Our results indicated reduced mortality and clinical disease severity in mice treated with antibiotics compared with untreated mice. Our findings support the hypothesis that there are reciprocal effects between experimental CNS inflammatory demyelination and modification of the microbiome providing a foundation for the establishment of early therapeutic interventions targeting the gut microbiome that could potentially limit disease progression.